PENGARUH DIVERSIFIKASI PORTOFOLIO KREDIT TERHADAP TINGKAT RISIKO KREDIT DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI (Studi pada Bank Umum di Indonesia) - Widyatini, Ignatia Ryana (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2015)
A formal control system supports the success of loan portfolio diversifcation strategy. Good corporate governance as a formal control system can support the success of the implementation of loan portfolio diversifcation strategy.Ã‚Â ThisÃ‚Â willÃ‚Â result in the low level of risk profle. The aim of this study is to explore the efect of loan portfolio diversifcation on the credit risk level with good corporate governance as a moderating variable. EViews 7.2 was used in the panel data analysis. General banks that had registered at BEI in the 2009-2012 period were used as samples. Data collection of 20 banks was based on certain criteria. The results of this research showed that good corporate governance moderate loan portfolio diversifcation strategy, so it can decrease t h eÃ‚Â credit risk level. The positive efect of good corporate governance in moderating the efect of loan portfolio diversifcation on theÃ‚Â credit risk level was consistent, not only based on the type of loan but also the economic sector.Keywords: loan portfolio diversifcation, credit risk, good corporate governanc.